Phylogeography of the crown-of-thorns starfish in the Indian Ocean. - Catherine Vogler; John Benzie; Paul H Barber; Mark V Erdmann; Ambariyanto; Charles Sheppard; Kimberly Tenggardjaja; Karin Gérard; Gert Wörheide (PLoS ONE, 2012)
Understanding the limits and population dynamics of closely related sibling species in the marine realm is particularly relevant in organisms that require management. The crown-of-thorns starfish Acanthaster planci, recently shown to be a species complex of at least four closely related species, is a coral predator infamous for its outbreaks that have devastated reefs throughout much of its Indo-Pacific distribution.In this first Indian Ocean-wide genetic study of a marine organism we investigated the genetic structure and inferred the paleohistory of the two Indian Ocean sister-species of Acanthaster planci using mitochondrial DNA sequence analyses. We suggest that the first of two main diversification events led to the formation of a Southern and Northern Indian Ocean sister-species in the late Pliocene-early Pleistocene. The second led to the formation of two internal clades within each species around the onset of the last interglacial. The subsequent demographic history of the two lineages strongly differed, the Southern Indian Ocean sister-species showing a signature of recent population expansion and hardly any regional structure, whereas the Northern Indian Ocean sister-species apparently maintained a constant size with highly differentiated regional groupings that were asymmetrically connected by gene flow.Past and present surface circulation patterns in conjunction with ocean primary productivity were identified as the processes most likely to have shaped the genetic structure between and within the two Indian Ocean lineages. This knowledge will help to understand the biological or ecological differences of the two sibling species and therefore aid in developing strategies to manage population outbreaks of this coral predator in the Indian Ocean.